Flavobacterium plurextorum sp. nov. Isolated from Farmed Rainbow Trout (Oncorhynchus mykiss). - Leydis Zamora; José F Fernández-Garayzábal; Cristina Sánchez-Porro; Mari Angel Palacios; Edward R B Moore; Lucas Domínguez; Antonio Ventosa; Ana I Vela (PLoS ONE, 2013)
Five strains (1126-1H-08(T), 51B-09, 986-08, 1084B-08 and 424-08) were isolated from diseased rainbow trout. Cells were Gram-negative rods, 0.7 µm wide and 3 µm long, non-endospore-forming, catalase and oxidase positive. Colonies were circular, yellow-pigmented, smooth and entire on TGE agar after 72 hours incubation at 25°C. They grew in a temperature range between 15°C to 30°C, but they did not grow at 37°Cor 42°C. Based on 16S rRNA gene sequence analysis, the isolates belonged to the genus Flavobacterium. Strain 1126-1H-08(T) exhibited the highest levels of similarity with Flavobacterium oncorhynchi CECT 7678(T) and Flavobacterium pectinovorum DSM 6368(T) (98.5% and 97.9% sequence similarity, respectively). DNA-DNA hybridization values were 87 to 99% among the five isolates and ranged from 21 to 48% between strain 1126-1H-08(T), selected as a representative isolate, and the type strains of Flavobacterium oncorhynchi CECT 7678(T) and other phylogenetic related Flavobacterium species. The DNA G+C content of strain 1126-1H-08(T) was 33.2 mol%. The predominant respiratory quinone was MK-6 and the major fatty acids were iso-C15∶0 and C15∶0. These data were similar to those reported for Flavobacterium species. Several physiological and biochemical tests differentiated the novel bacterial strains from related Flavobacterium species. Phylogenetic, genetic and phenotypic data indicate that these strains represent a new species of the genus Flavobacterium, for which the name Flavobacterium plurextorum sp. nov. was proposed. The type strain is 1126-1H-08(T) ( = CECT 7844(T) = CCUG 60112(T)).